A gift is not always a gift: Gift exchange in a voucher experiment - Sascha O. Becker; Dolores Messer; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2011)
Different from traditional gift exchange experiments, we study a field experiment where a random subsample of participants in the Swiss Labor Force Survey was sent vouchers to be used in adult training courses. Importantly for our purposes, actual voucher redemption can be traced. This gives the unique opportunity to study whether gift exchange in the form of participation in future rounds of the survey depends on the perceived usefulness of the gift. We find that the group of voucher recipients as a whole has significantly higher response rates in the survey six months after the vouchers were sent out. There is considerable heterogeneity, though. Our results point to a long-lasting gift exchange relationship for the sub-group that had redeemed their vouchers. Contrary to this group, the individuals who did not redeem their vouchers, had a response pattern that was not significantly different from the voucher non-recipients.
Keywords: C42; C93; Z13; 330; gift exchange; reciprocity; field experiment; long-run effects